(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Women Entrepreneurship (WE) in India has emerged as a significant contributor to economic growth and social development. This research highlights WE in India and also focuses on the challenges and opportunities faced by women entrepreneurs in India. The research discusses the current scenario of WE in India and reviews various literature to gain insights into the topic. The research incorporated the primary quantitative and secondary qualitative data collection methods to examine the perception of various groups of individuals concerning WE and also determine the challenges and opportunities faced by women entrepreneurs. The primary data is analysed using statistical analysis methods, and the secondary data is analysed using thematic analysis. The findings underscore the need for targeted interventions to empower women entrepreneurs, enabling them to overcome obstacles and leverage opportunities for sustainable growth and development. Based on these findings, the research has also provided actionable recommendations to boost women’s entrepreneurial activities in India.